Modern preoperative evaluation in ambulatory surgery – who, where and how?. Issue 6 (4th December 2022) - Filipovic, Mark G.; Schwenter, Aline; Luedi, Markus M.; Urman, Richard D.
Abstract : Purpose of review: Ambulatory surgery is increasingly performed in medically complex patients. This dynamic environment requires new approaches to ensure cost-effective, efficient, and ultimately safe preoperative evaluation of the patient. This review investigates recent advances in the assessment of ambulatory patients, with a special focus on patient screening, digital communication, and multidisciplinary team evaluation. Recent findings: Identifying suitable candidates for ambulatory surgery relies on a variety of medical, surgical, and institutional factors. Identification of high-risk patients and optimization of their treatment can be achieved through multidisciplinary protocols specific to the local institution and in line with current guidelines. Virtual assessment may be sufficient for most patients and provide an efficient evaluation strategy and high patient satisfaction. Prescreening can be supported by preoperative nursing teams. Summary: The increasing complexity of treatment provided in day surgery offers a unique opportunity to highlight the importance of anesthesiology staff as perioperative caregivers. Preoperative evaluation serves as a central junction to integrate a variety of surgical, medical, and institutional factors to provide safe, satisfactory, and efficient care for patients. Implementing technological innovation to streamline and facilitate this process is paramount.